An Investigation on Design and Analysis Overground Water Pipeline Steel Bridge - Omar, Najiy; Jamaluddin, Norwati (Recent Trends in Civil Engineering and Built Environment, 2021)
The purpose for this project was to design an over ground steel pipeline bridge for water distribution network system. The work consisted of the determination of design parameters and the design of the superstructure of the bridge and a recommended construction plan. The final design of the over ground steel pipeline bridge is a Warren and Pratt truss bridge composed of a total 40 m and a width of 2 m span. The truss is made up of steel materials and I sections with both fixed end connections. The pipeline bridge is to be located at Terengganu for the project of Bekalan Air Kuala Terengganu. Next, for the aerial pipeline crossing supports a water pipeline with a diameter of 500 mm and a thickness of 30 mm. In the design of the superstructure, trusses were selected as the most suitable option amongst the possible bridge systems. These bridge systems were evaluated at the conceptual stage. BS EN 1993-1-1:2005 was the code used in the design of the superstructure by using Staad Pro modelling analysis. Regarding our case study, a total of 3 load combination were used in this design and analysis which was ultimate limit strength (maximum), ultimate limit strength (minimum) and stress limit strength. While for the design loads, it can be determined from the Staad Pro results and the design of pile cap was designed using Staad Pro foundation software by inserting the reaction forces obtain from the analysis. Using beam method, approximate component sizes and reinforcement requirements for the pile cap were determined. A calculation for determine shear forces, bending and selection for the reinforcement of both design bridge after complete the analysis. The complete analysis was performed to have configuration in determine the optimal panel widths, depths and the initial size of the preliminary members. It was found that the Warren truss was the perfect and suitable design that provided the most economical solution while meeting the deflection requirements specified by the pipeline designer.